Results from the worldwide coma morphology campaign for comet ISON (C/2012 S1). (1st December 2015) - Samarasinha, Nalin H.; Mueller, Beatrice E.A.; Knight, Matthew M.; Farnham, Tony L.; Briol, John; Brosch, Noah; Caruso, John; Gao, Xing; Gomez, Edward; Lister, Tim; Hergenrother, Carl; Hoban, Susan; et al.
Abstract: We present the results of a global coma morphology campaign for comet C/2012 S1 (ISON), which was organized to involve both professional and amateur observers. In response to the campaign, many hundreds of images, from nearly two dozen groups were collected. Images were taken primarily in the continuum, which help to characterize the behavior of dust in the coma of comet ISON. The campaign received images from January 12 through November 22, 2013 (an interval over which the heliocentric distance decreased from 5.1 AU to 0.35 AU), allowing monitoring of the long-term evolution of coma morphology during comet ISON׳s pre-perihelion leg. Data were contributed by observers spread around the world, resulting in particularly good temporal coverage during November when comet ISON was brightest but its visibility was limited from any one location due to the small solar elongation. We analyze the northwestern sunward continuum coma feature observed in comet ISON during the first half of 2013, finding that it was likely present from at least February through May and did not show variations on diurnal time scales. From these images we constrain the grain velocities to 10 m s −1, and we find that the grains spent 2–4 weeks in the sunward side prior to merging with the dust tail. We present a rationale for the lack of continuum coma features from September until mid-November 2013, determining that if the feature from the first half of 2013 was present, it was likely too small to be clearly detected. We also analyze the continuum coma morphology observed subsequent to the November 12 outburst, and constrain the first appearance of new features in the continuum to later than November 13.99 UT.